Phaseolus vulgaris mutants reveal variation in the nuclear genome - Tomlekova, Nasya; Idziak-Helmcke, Dominika; Franke, Paula; Rojek-Jelonek, Magdalena; Kwasniewska, Jolanta (Frontiers in Plant Science, 2024)
Phaseolus vulgaris L. (common bean) is an essential source of proteins in the human diet worldwide. Bean breeding programs to increase genetic diversity based on induced mutagenesis have a long tradition in Bulgaria. Common bean varieties with high productivity, wide environmental adaptability, good nutritional properties, and improved disease resistance have been successfully developed. In this study, we aimed to investigate selected nuclear genome features, such as the genome size, the number and chromosomal distribution of 5S and 35S rDNA loci by using the fluorescence in situ hybridization (FISH), as well as the level of DNA damage in some local Bulgarian accessions and mutants of P. vulgaris. Flow cytometry analyses revealed no significant differences in genome size between analyzed lines except for one of the analyzed mutants, M19. The value of genome size 2C DNA is about 1.37 pg2C -1 for all lines, whereas it is 1.42 pg2C -1 for M19. The chromosome number remains the same (2n=22) for all analyzed lines. Results of FISH analyses showed that the number of 5S rDNA was stable among accessions and mutant lines (four loci), while the number of 35S rDNA loci was shown as highly polymorphic, varying between ten and sixteen, and displaying differences in the size and location of 35S rDNA loci between analyzed genotypes. The cell cycle profile was different for the analyzed genotypes. The results revealed that wide variation in genome organization and size as well as DNA damage characterizes the analyzed genetic resources of the common bean.